Effect of cuprum on the microstructure and properties of iron-based hardfacing alloys deposited by plasma transferred ARC process; Modern technique and technologies MTT' 2012 - Isakin I. A. (Section III: Technology, Equipment and Machine Building Production Automation, 2012)
Заглавие с титульного листа